(untitled) (Research, Society and Development, 2021)
The study aims to build an instrument to support the nursing process in Sexually Transmitted Infections. This is a quantitative and transversal study of a methodological type organized in five stages: identification of empirical evidence, selection of relevant variables for anamnesis and physical examination, preparation of diagnoses, results and nursing interventions, construction of the initial version of the instrument and validation content of the instrument. The construction of the instrument was based on the Theory of Basic Human Needs and the empirical material was the Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections. For the proposition of diagnoses, results and interventions, the International Classification for Nursing Practice was used. In addition, correspondence was prepared in accordance with the International Classification of Primary Care, with a view to its application in primary care during the nursing consultation. The instrument includes relevant items for the nursing consultation, covering sexuality, genitourinary changes, testing, immunization and STI counseling. It is expected to promote the qualification of care in STIs from the use of a data collection instrument during the nursing consultation, specifically for patients affected by asymptomatic STIs, in order to guide the actions to be performed by the professional as recommended by the protocol national clinician.